Co-offenders’ crime location choice: do co-offending groups commit crimes in their shared awareness space? - Lammers, Marre (The British journal of criminology, 2018)
This study examines the influence of co-offending on crime location choice: the extent to which awareness spaces of co-offenders overlap and whether co-offended crimes are more likely committed in this overlap in awareness space. In total, 4,654 offenders from the greater The Hague region in The Netherlands were studied. They committed 6,283 crimes; of which, 3,612 were co-offended. The data were analysed using a discrete spatial choice model. Results show that most co-offending groups share 50 per cent or less of their awareness space. Offender groups are significantly more likely to commit crimes in areas known to multiple offenders in the group (the shared awareness space of the group) than in areas known to one offender or none of the offenders.